2014
DOI: 10.1186/1471-2407-14-218
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Up-regulated miR-199a-5p in gastric cancer functions as an oncogene and targets klotho

Abstract: BackgroundRecent studies have shown that miR-199a-5p plays opposite roles in cancer initiation and progression of different cancer types, acting as oncogene for some cancer types but as tumor suppressor gene for others. However, the role and molecular mechanism of miR-199a-5p in gastric cancer are largely unknown.MethodsIn this study, miR-199a-5p expression level in gastric cancer was first analyzed by qPCRand then validated in 103 gastric cancer patients by in situ hybridization (ISH). Gastric cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 29 publications
2
72
0
Order By: Relevance
“…Hu et al reported that miR-199a-5p was frequently downregulated in colorectal cancer, which led to the upregulation of discoidin domain receptor 1 and the activation of epithelialto-mesenchymal transition-related signaling (16). In addition, the expression level of miR-199a-5p was significantly increased in gastric cancer tissues compared with paired normal tissues, and higher miR-199a-5p level was associated with increased lymph node metastasis and higher tumor-node-metastasis stage, suggesting that miR-199a-5p may act as an oncogene in gastric cancer (26). Recently, miR-199a-5p has been reported to exhibit inhibitory effects on autophagy (27).…”
Section: Mir-199a-5p Negatively Mediates the Protein Expression Of Bementioning
confidence: 98%
“…Hu et al reported that miR-199a-5p was frequently downregulated in colorectal cancer, which led to the upregulation of discoidin domain receptor 1 and the activation of epithelialto-mesenchymal transition-related signaling (16). In addition, the expression level of miR-199a-5p was significantly increased in gastric cancer tissues compared with paired normal tissues, and higher miR-199a-5p level was associated with increased lymph node metastasis and higher tumor-node-metastasis stage, suggesting that miR-199a-5p may act as an oncogene in gastric cancer (26). Recently, miR-199a-5p has been reported to exhibit inhibitory effects on autophagy (27).…”
Section: Mir-199a-5p Negatively Mediates the Protein Expression Of Bementioning
confidence: 98%
“…Moreover, the ectopic expression of p53 induces miR199a transcription, and then affects the restructuring of mouse embryonic fibroblasts (Wang et al, 2012). Recent research also found that miR-199a-5p can promote gastric cancer by inhibition of Klotho protein expression (He et al, 2014). Besides, can modulate the process of renal fibrosis (Christian et al, 2013) and the growth of kidney cancer cells (Tsukigi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another study also showed that miR-199a-5p was significantly down-regulated in advanced stage in small cell carcinoma of the cervix [34]. In contrast, expression of miR-199a-5p was increased in gastric cancer and it is associated with human gastric tumor development [12]. Similar with ovarian cancer and hepatocellular carcinoma, loss of miR-199a-5p expression may have an important role in pathogenesis of cSCC.…”
Section: Discussionmentioning
confidence: 95%
“…The miR-199a precursor produces mature miRNAs named miR-199a-5p and miR-199a-3p [9]. The results of several studies support a critical role for miR-199a in various cell types and tissues including the liver, stomach, ovary, and testis [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 90%